Guideline for Occupational Enhancement for the Elderly in Andaman Province; Case Study in Phuket, Phang Nga and Krabi - Yamsrisuk, Chalida; Muenpun, Ratchaneewan; Thahong , Waranya; Kayem, Pattaramon (Interdisciplinary Academic and Research Journal, 2023)
Facilitating career advancement opportunities that align with the capabilities of older individuals is crucial in enabling them to generate income and achieve self-sufficiency. Simultaneously, it has the potential to generate cognitive benefits for the elderly population. Experiencing a sense of self-esteem and contentment with one’s existence. This intervention has the potential to enhance the quality of life for older adults. Hence, this study aims to examine the potential and occupational requirements of the elderly population residing in Andaman Province, as well as to investigate the guidelines for enhancing their career prospects in the region. A sample of 90 persons participated in this mixed-method study that included questionnaires, in-depth interviews, and focus groups as research instruments. (1) The study’s findings indicate that certain occupations serve as a means of supplementing the income required by the elderly. The subject matter pertains to the product. The study found that the highest proportion of occupations in the sample were related to health care (27.78%) and handicrafts (27.78%). Occupations related to food and drink represented 22.22% of the sample, while other work had the lowest representation at 5.56%. (2) Research on the elderly population in Andaman has revealed that they possess valuable local knowledge and are eager to share it. The categorization of wisdom across different domains can be delineated as follows. The primary areas of focus among the surveyed population were cooking, accounting for 25.56 percent of responses, followed by agriculture at 23.33 percent. Additionally, respondents expressed interest in developing their knowledge of weaving, handicrafts, weaving, and embroidery. The creation of Batik painted Sandalwood flowers, wreath-making, and confetti production resulted in a 12.22 percent output. Furthermore, there exists knowledge about the treatment of illnesses, the use of medicinal plants, physical activities, angling, sculpting, metalworking, building, and the production of paper utilizing natural waste materials. (3) The guidelines aimed at improving the career prospects of the elderly should be aligned with their potential and career requirements. 1) Facilitating intergenerational knowledge transfer by leveraging the experiential wisdom of the elderly. 2) Revitalizing traditional culinary practices, non-toxic agricultural techniques, handicrafts, and weaving machinery to promote the preservation of local desserts and food processing methods. 3) Enabling the younger cohort to engage in the process through the utilization of technology, specifically online marketing. The transportation and distribution of goods to regional hubs and other designated locations. And (4) Recommendations for implementing the study findings to advance individuals’ well-being across the lifespan. Collaboratively engage in elderly care within the community. The utilization of technology to expand the distribution channels for products manufactured by the elderly is a noteworthy consideration. Additionally, local government organizations must prioritize efforts aimed at supporting the elderly workforce. Establishing a network of social connections among the elderly population residing in Andaman Province to foster a platform for knowledge exchange. Facilitate novel viewpoints that can foster the ongoing enhancement of the elderly’s potential.